Pengaruh Akuntabilitas dan Manajemen Zakat Terhadap Zakat Produktif dengan Sharia Compliance sebagai Pemoderasi - Husnul Khatimah; Lince Bulutoding; Suhartono (Income Journal: Accounting, Management and Economic Research, 2023)
This study aims to determine the effect of accountability and zakat management on productive zakat management with shari compliance as a moderating variable. This research is located in BAZNAS Makassar City. The method used is quantitative reseach with a causality approach. Primary data sources with data collection methods using questionnaires. The sampling technique is saturated sampling with a total of 30 respondents. The results of the study show that accountability has a positive and significant effect on productive zakat management. Zakat management has a positive and significant effect on productive zakat management. Sharia compliance moderates the relationship between accountability to productive zakat management.